Benign Recurrent Intrahepatic Cholestasis (BRIC): An African Case Report. (10th March 2020) - Salyani, Adil; Barasa, Linda; Rajula, Allan; Ali, Sayed K.
Abstract : Benign recurrent intrahepatic cholestasis (BRIC) is a rare disorder characterised by recurrent episodes of cholestatic jaundice. First described in 1959, BRIC has been reported in patients all over the world including of African descent. Here, we describe a case of a 21-year-old male with recurring episodes of cholestatic jaundice where we diagnosed BRIC and terminated an episode with rifampicin. To our knowledge, this is the first case report of BRIC diagnosed in Africa.